Fluid identities and transnational belonging in Khaled Hosseini’s The Kite Runner - Surya Akther Sumona (Universitas Merdeka Malang, 2025)
Khaled Hosseini’s The Kite Runner (2003) illustrates how war, displacement, and exile contribute to the formation of transnational identities. The novel also captures the profound anguish experienced by migrants. As an Afghan-American, Hosseini narrates his personal understanding of Afghanistan’s political, social, and religious turmoil, vividly portraying these realities in this novel. This research will examine the formation of transnational identity and the challenges inherent in the migration process by focusing on the fractured lives of Afghan migrants, who are compelled to navigate shifting cultural, political, and emotional landscapes. It will draw on the theories of diaspora (Stuart Hall), and imaginary homelands (Salman Rushdie) to demonstrate how Hosseini portrays identity as both rooted in a shared past and continually reconstructed through experiences of dislocation and diaspora. Hosseini has not represented migration simply as a physical crossing of border but also a psychological rupture that produces nostalgia and the struggle for belonging.